Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume-III Government of Manipur - Planning Commission (Planning Commission, 1985)
Draft Seventh Five Year Plan 1985-90 And Annual Plan 1985-86 Heads Of Development -State/Union Territories Outlay And Expenditure Draft Seventh Five Year Plan (1985-90) And Annual Plan 1935-86 Drift Seventh Plan (1985-90) And Annual Plan 1985-86 Employment Content Of Sectral. Programme 1985-86 Target And Achievement
Planning Department Govt. of Manipur